Enhanced β-adrenergic cardiac reserve in Trpm4−/− mice with ischaemic heart failure. (19th January 2015) - Jacobs, Griet; Oosterlinck, Wouter; Dresselaers, Tom; Geenens, Rachel; Kerselaers, Sara; Himmelreich, Uwe; Herijgers, Paul; Vennekens, Rudi
Abstract: Aims: Heart failure (HF) is a complex syndrome characterized by critically reduced cardiac contractility and function. We have shown previously that Transient Receptor Potential Melastatin 4 protein (TRPM4) functions as a Ca 2+ -activated non-selective cation channel and constitutes a novel regulator of ventricular contractility. In healthy Trpm4 -deficient ( Trpm4 −/− ) mice, we observed increased cardiac contractile function after β-adrenergic stimulation. In the current study, cardiac performance was examined in wild-type (WT) and Trpm4 −/− mice with severe ischaemic HF. Methods and results: Myocardial infarction (MI) was induced in WT and Trpm4 −/− C57Bl6/N mice by ligation of the left anterior descending artery. During the first week after MI, mortality was higher in WT mice. Both groups showed similar infarct-typical ECG patterns during follow-up period. After 10 weeks, reduced ejection fraction and severe dilatation, determined by cardiac MRI, confirmed the development of HF in both genotypes. In vivo pressure-conductance analysis revealed no differences in cardiac contractility in basal conditions. However, during β-adrenergic stimulation, cardiac performance was significantly different between WT and Trpm4 −/− mice. In contrast to increasing contractility in Trpm4 −/− mice, WT mice showed a deteriorated cardiac performance. Also 30% of WT animals died during isoprenaline infusion vs. no Trpm4 −/− mice. Infarct size, determined post mortem, was equal in WT and Trpm4 −/− hearts. Conclusion: Deletion of the Trpm4 gene in mice improved survival and significantly enhanced β-adrenergic cardiac reserve after inducing ischaemic HF. This suggests that pharmacological or genetic down-regulation of TRPM4 function might be a novel strategy in the management of HF.